РОЗВИТОК МОВЛЕННЄВИХ ЗДІБНОСТЕЙ МОЛОДШИХ ШКОЛЯРІВ У ТЕАТРАЛЬНО-ІГРОВІЙ ДІЯЛЬНОСТІ (Педагогіка вищої та середньої школи, 2022)
Content, structure, diagnostics, and methodics of the work on development o f theatrical \ actor skills in preschool children is exposed to theoretical and experimental study.